Deep Infrapatellar Bursitis in Preadolescent Baseball Players: A Cross-Sectional Study. Issue 3 (17th March 2022) - Omae, Hiroaki; Ohsawa, Takashi; Omodaka, Takuya; Hashimoto, Shogo; Oshima, Atsufumi; Takase, Ryota; Kobayashi, Hiroki; Takamine, Shuhei; Tajika, Tsuyoshi; Chikuda, Hirotaka
Background: Deep infrapatellar bursitis (DIB) has been detected in cases of Osgood-Schlatter disease (OSD). However, the clinical implications of DIB in the apophyseal stage, during the period when OSD has not yet developed, remain unclear. Purpose: To investigate the factors related to DIB in the apophyseal stage in preadolescent baseball players. Study Design: Cross-sectional study, Level of evidence, 3. Methods: The study participants were junior baseball players who participated in a medical checkup in 2020. We included knees in the apophyseal stage evaluated using ultrasonography, and classified them into the bursitis and no-bursitis groups using color-enhanced Doppler ultrasonography. We also investigated bone lesions of the tibial tuberosity, determined by fragmentation of the bone and irregularity of the ossification center. Demographic data, practice duration, pressure pain on tuberosity, pain while playing baseball (visual analog scale), heel-buttock distance (HBD), straight-leg raise angle, and range of hip internal and external rotation were evaluated. Group comparisons were performed using the Mann-Whitney U test and Fisher exact test, and a logistic regression analysis was performed. Results: A total of 261 knees (139 male players; age 10.5 ± 1.1 years) were included, 30 in the bursitis group and 231 in the no-bursitis group. Bone lesions were present in 4 knees in the bursitis group and in 32 knees in the no-bursitis group; there was no significant relationship between the presence of bone lesions and bursitis. Compared with the no-bursitis group, the bursitis group had a significantly longer practice duration (12.9 ± 3.3 vs 15.2 ± 3.8 hours/week, respectively; P = .003) and larger HBD (0.5 ± 1.3 vs 1.4 ± 2.4 cm, respectively; P = .003). The logistic regression analysis showed that practice duration ( P = .001) and HBD ( P = .004) were significantly related to the presence of bursitis. Conclusion: DIB in the apophyseal stage was related to practice duration and thigh muscle tightness. These findings may help predict overload and thigh muscle tightness at a very early stage.